STUDENTS AND PARENTS’ PERCEPTIONS TOWARD ENGLISH ONLINE LEARNING DURING CORONA VIRUS PANDEMIC - Liando, Nihta V. F.; Pelenkahu, Noldy; Mongkaren, Steve (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
E-learning dramatically changes the learning process. As a result, both teachers and students have to work hard to adapt to the process. In response to these changes, this study aims to analyze the perceptions of junior high school, senior high school, and parents regarding online learning. This study involved 44 parents, 24 junior high school students, and 20 high school students. Data were collected using two questionnaires. The data collected were analyzed quantitatively in the form of percentages. The results of data analysis show that junior high school students use computers/devices for online learning activities; however, they consider traditional methods (live class meetings) to be more appropriate than online learning. (2) High school students also use their computers/devices for online learning and have full support from their teachers, but they prefer traditional methods. They consider traditional methods more effective than online learning, and (3) parents prefer traditional methods over online learning. Therefore, teachers are advised to be creative in teaching online; parents are expected to continue to control their students' online learning. More research is needed so that more information about online learning can be obtained.